2015
DOI: 10.3389/fnins.2015.00183
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone is associated with cooperation during intergroup competition by enhancing parochial altruism

Abstract: The steroid hormone testosterone is widely associated with negative behavioral effects, such as aggression or dominance. However, recent studies applying economic exchange tasks revealed conflicting results. While some point to a prosocial effect of testosterone by increasing altruistic behavior, others report that testosterone promotes antisocial tendencies. Taking into account additional factors such as parochial altruism (i.e., ingroup favoritism and outgroup hostility) might help to explain this contradict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
47
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 29 publications
(59 reference statements)
8
47
2
1
Order By: Relevance
“…Additional evidence with more salient ingroups come from Dominica, where men playing dominoes against competitors from neighbouring villages tended to have larger increases in testosterone than individuals playing against competitors from their home community [117]. A recent study found that acute increases in testosterone can increase cooperation within an in-group via increased parochial altruism when facing a potential out-group [119]. Interestingly, research conducted among Tsimané, where community membership is fluid and community-based competitions often pit men against their kin, show no evidence of a team-based winner effect [98].…”
Section: (C) Testosterone and Intergroup Competitionmentioning
confidence: 99%
“…Additional evidence with more salient ingroups come from Dominica, where men playing dominoes against competitors from neighbouring villages tended to have larger increases in testosterone than individuals playing against competitors from their home community [117]. A recent study found that acute increases in testosterone can increase cooperation within an in-group via increased parochial altruism when facing a potential out-group [119]. Interestingly, research conducted among Tsimané, where community membership is fluid and community-based competitions often pit men against their kin, show no evidence of a team-based winner effect [98].…”
Section: (C) Testosterone and Intergroup Competitionmentioning
confidence: 99%
“…These results also support a growing body of evidence that people are more likely to prevent outgroup members obtaining monetary rewards, relative to ingroup members. People are more likely to reject offers in the UG from outgroups, and the rejection of UG offers increases with increasing social distance to the outgroup (De Dreu et al., 2010; Everett et al., 2015; Kubota, Li, Bar‐David, Banaji, & Phelps, 2013; Mendoza, Lane, & Amodio, 2014; Reimers & Diekhof, 2015; Yamagishi & Mifune, 2016) . Behaviorally our results support such findings, underscoring the powerful effects that group membership has on the willingness to be altruistic toward others.…”
Section: Discussionmentioning
confidence: 99%
“…This effect of testosterone on human cooperation was more evident in participants with little prenatal exposure to testosterone (this was verifi ed via the 2D:4D ratio). Reimers and Diekhof (2015) recently verifi ed the role of testosterone in ingroup favoritism involving soccer fans. During the prisoner's dilemma game, players with high testosterone levels increased their ingroup cooperation when exposed to intergroup competition.…”
Section: Neuroendocrine Mechanisms Underlying Group Biasmentioning
confidence: 99%